ASSESSMENT OF THE CURRENT SYSTEM OF INVESTMENT PLANNING OF BUSINESS ACTIVITIES OF FUEL AND ENERGY COMPLEX OF THE REPUBLIC OF CRIMEA - Irina Rodenko (Вестник Северо-Кавказского федерального университета)
The article analyzes the current state of the fuel and energy complex of the Republic of Crimea, presents the dynamics of investment in the fuel and energy complex of the Republic of Crimea since 2006 year till 20l7year, the current system of investment design of business activity was evaluated. Also in the article the organizational structure of fuel and energy Complex of the Republic of Crimea is detailed, the main problems preventing attraction of investments in fuel and energy complex of the Republic of Crimea are revealed, the model of secondary use of means of investment design is offered; the main indicators of activity of the fuel and energy companies influencing sustainable development of the Republic of Crimea.